The night before Christmas - Moore, Clement Clarke, 1779-1863 (Simon & Schuster Books for Young Readers, 1997)
The illustrator's Vermont farmhouse and her pets are featured in the illustrations of this well-known poem about an important Christmas Eve visitor.